2021
DOI: 10.1111/1475-6773.13866
|View full text |Cite
|
Sign up to set email alerts
|

The effect of data aggregation on estimations of nurse staffing and patient outcomes

Abstract: Objective: To examine how estimates of the association between nurse staffing and patient length of stay (LOS) change with data aggregation over varying time periods and settings, and statistical controls for unobserved heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…This study makes contributions beyond those of the existing literature on the relationship between nurse staffing and patient outcomes in three respects: First, although the aggregation and omitted variable biases (due to aggregating different frequencies data into single frequency data) have attracted lots of attention regarding the estimation of the nurse staffing and patient outcomes relationship in the healthcare services research field [39], this study, for the first time, adopted the MF-VAR model proposed by Ghysel and his colleagues [47,48] to incorporate different frequencies data into the investigation of the relationships among PNR, ICQ, and real ICE per admission under the GBPS of Taiwan's NHI system over the period of 2015:Q1-2021:Q4. We illustrated that the MF-VAR model is superior to the LF-VAR (i.e., conventional VAR) model in terms of higher explanatory power (See Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study makes contributions beyond those of the existing literature on the relationship between nurse staffing and patient outcomes in three respects: First, although the aggregation and omitted variable biases (due to aggregating different frequencies data into single frequency data) have attracted lots of attention regarding the estimation of the nurse staffing and patient outcomes relationship in the healthcare services research field [39], this study, for the first time, adopted the MF-VAR model proposed by Ghysel and his colleagues [47,48] to incorporate different frequencies data into the investigation of the relationships among PNR, ICQ, and real ICE per admission under the GBPS of Taiwan's NHI system over the period of 2015:Q1-2021:Q4. We illustrated that the MF-VAR model is superior to the LF-VAR (i.e., conventional VAR) model in terms of higher explanatory power (See Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Second, these studies fail to provide precautionary information in terms of the propagation mechanism of a nurse staffing policy shock across a period of time. Third, a recent study proposed by Winter and his colleagues cautioned against a potential data aggregation effect on estimations of the nurse staffing and patient outcomes relationship [39]. Moreover, nurse staffing and patient outcomes can be reported in different time frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The weak correlation between FTE midwives and ward level CHPPD is interesting as we expected this to be more closely related. However, this is not an unusual finding as recent research from the USA has also discovered differences in the performance of staffing measures, and called for validated measures to be used[34] Winter et al[23] found that estimates of staffing and outcomes were larger and more precise when data is disaggregated. This has not been found in our study despite the expectation of gaining more clarity with localised data at a ward level.…”
Section: Discussionmentioning
confidence: 99%
“…We found no published studies examining the impact of staffing measured at a postnatal ward level, which is expected to provide a more accurate measurement of staffing exposure. A study by Winter et al [23] found that aggregation of data changes the magnitude of estimation when examining the association between staffing and outcomes. Point estimates for associations were larger in magnitude when more precise data on staffing was used.…”
Section: Introductionmentioning
confidence: 99%
“…1 In minutes2 Categorical variables (units, days, and months) were coded using sum contrasts. Each level in the table reflects deviation from the grand-mean.…”
mentioning
confidence: 99%